Hyaluronan signaling and turnover - Simpson, Melanie A. (Advances in cancer research, 2014)
Advances in Cancer Researchprovides invaluable information on the exciting and fast-moving field of cancer research. Here, once again, outstanding and original reviews are presented on a variety of topics. This volume covers hyaluronan signaling and turnover. Provides information on cancer researchOutstanding and original reviewsSuitable for researchers and students